Interaction of Pubertal Development and Metabolic Control in Adolescents with Type 1 Diabetes Mellitus - M. Plamper; B. Gohlke; J. Woelfle; K. Konrad; T. Rohrer; S. Hofer; W. Bonfig; K. Fink; R. W. Holl (Journal of Diabetes Research)
Background. In T1DM, delayed pubertal development and reduced final height are associated with inadequate metabolic control. Objective. To assess whether T1DM affects pubertal growth spurt and whether metabolic control during puberty is gender-related. Methods. Using a large multicentre database, longitudinal data from 1294 patients were analysed. Inclusion criteria: complete records of height and HbA1c from the age of seven to 16 years. Exclusion criteria: other significant chronic diseases and medications, T1DM duration less than three months, and initial BMI < 3rd or >97th percentile. Results. Growth velocity (GV) was impaired with a significant reduction of peak GV by 1.2 cm in boys. HbA1c increase during male puberty was lower except for a period of 1.5 years. The highest HbA1c increase in boys coincided with maximum growth spurt. In girls, the highest HbA1c increase was observed during late puberty. Even though there is impaired GV, both sexes reach a height at 16 years of age which corresponds to the background population height. Conclusion. Worsening of metabolic control is sex-discordant and associated with gender-specific alterations of GV. However, the vast majority of boys and girls with T1DM seems to reach normal height at the age of 16 years.